Предмет:
МатематикаАвтор:
анонимУпростим выражение (2 * а - b)^3 + (2 * a + b)^3.
Раскроем скобки и приведем подобные значения.
(2 * а - b)^3 + (2 * a + b)^3 = (2 * a)^3 - 3 * (2 * a)^2 * b + 3 * 2 * a * b^2 - b^3 + (2 * a)^3 + 3 * (2 * a)^2 * b + 3 * 2 * a * b^2 + b^3 = 8 * a^3 - 12 * a^2 * b + 6 * a * b^2 - b^3 + 8 * a^3 + 12 * a^2 * b + 6 * a * b^2 + b^3 = 8 * a^3 - 12 * a^2 * b + 6 * a * b^2 + 8 * a^3 + 12 * a^2 * b + 6 * a * b^2 = 8 * a^3 + 6 * a * b^2 + 8 * a^3 + 6 * a * b^2 = a^3 * (8 + 8) + a * b^2 * (6 + 6) = 16 * a^3 + 12 * a * b^2.
Автор:
jonathonparsonsДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть